The Artistic Decoration of Armenian Medieval Architecture (12th - 14th Centuries) - Narine Mkhitaryan (Journal of Architectural and Engineering Research)
The means of artistic decoration of the second stage of developed Armenian architecture (12th-14th centuries) are presented. The research aims to highlight the features characteristic of the given period through a general analysis of ornamental art. The scientific innovation lies in clarifying the general features and the origins of form creation in the decorative means characterizing a given period, which will enable the determination of the monument's date, even when bibliographic and lithological data are scarce. As a result of the examination, the means of artistic decoration, with their new manifestations, played an important role in the formation of the stylistic direction of that period. They were formed on the achievements of the previous phase, the Bagratuni period (9th-11th centuries), as a result of cultural interactions with neighboring countries and were inherited by the following centuries.